Difficulty Student Understand English Speech in the Second Semester of the English Study Program - astri, astri juraini; Abrar Muda, Muhammad; Rakhmyta, Yunie Amalia; Agustina, Aida (Jumper: Journal of Educational Multidisciplinary Research, 2024)
Listening is a crucial skill that needs to be mastered in English language acquisition. However, several obstacles hinder the mastery of listening, such as difficulties in comprehending spoken language. In this scenario, there are a significant number of students who cannot comprehend the English language. The objective of this study is to identify the factors that contribute to students' difficulty in comprehending spoken English. The participants of this study consisted of English major students enrolled in the second semester at STAIN Gajah Putih Takengon. The focus of this research was to investigate the challenges that these students encounter when comprehending spoken language in the listening domain. The research methodology employed is qualitative. Regarding the internal instruments, this study employs observation, tests, and interviews. Research findings indicate that there are multiple factors that contribute to students' inability to comprehend English speech. The primary factors that influence students' listening skills are lack of concentration, speaking speed, and originality. The conclusion that can be inferred from this study is that the speed of speech delivery and a lack of concentration in listening are contributing factors to difficulty in understanding speech.